Pyrene-based aggregation-induced emission luminogens and their applications. (8th April 2019) - Islam, Md. Monarul; Hu, Zhen; Wang, Qingsong; Redshaw, Carl; Feng, Xing
Abstract : Pyrene shows very weak or quenched fluorescence in the solid state, but it is possible to turn it to a bright solid emitter by using aggregation-induced emission (AIE) strategies. Abstract : "Unity is force" – Aesop. It is a common phenomenon that traditional chromophores exhibit high fluorescence in dilute solutions, yet luminescence is quenched at high concentrations or in the aggregate state, i.e. "aggregation-caused quenching" (ACQ). Tang reported the unusual photophysical observation that luminogens can exhibit weak or no fluorescence in solution, yet they are highly emissive in the aggregate or solid state; this is defined as aggregation-induced emission (AIE). The discovery of AIE helped solve the ACQ effect in traditional luminophores. Pyrene is an important polycyclic aromatic hydrocarbon (PAH), which exhibits very different photophysical behavior in solution versus the aggregate state, and the ACQ effect has played a dominant role in pyrene chemistry. The ACQ effect is harmful for some practical applications and is a challenge in organic light-emitting diodes (OLEDs) and light-emitting electrochemical cells, for which the effect is more severe in the solid state. Thus, how to overcome the ACQ effect observed in pyrene chemistry still remains a challenge. In this review, we discuss how following basic AIE mechanisms such as the restriction of intramolecular motion (RIM), excited-state intramolecular proton transfer (ESIPT), and twisted intramolecular charge transfer (TICT), can transform pyrene-based ACQ luminogens to AIE luminogens with excellent optical properties. Furthermore, prospective applications of pyrene-based AIEgens are discussed, as is the potential for designing new organic functional materials.